Effect of Ni and Mo on microstructure and mechanical properties of grey cast iron. (31st December 2023) - Ning, Hangbo; Li, Xiaoyan; Meng, Linggang; Jiang, Ailong; Ya, Bin; Ji, Shengchen; Zhang, Weiping; Du, Jizhu; Zhang, Xingguo
ABSTRACT: Alloying elements (Ni, Mo) were added to grey cast iron, and the effect of Ni, Mo on microstructure and mechanical properties were analysed in this study. When Ni was added alone, the precipitation of graphite was inhibited at the early stage of solidification, and part of graphite was formed between the dendrites, resulted in an uneven distribution of graphite. Ni played a role of solution strengthening and reduced the pearlite interlammer spacing, improved the mechanical properties. The addition of Mo refined the austenite dendrites and made the carbon unevenly distributed, which led to the abnormal growth of graphite. Mo increased the eutectoid supercooling degree, reduced the pearlite interlammer spacing and improved tensile strength. When Ni and Mo were added together, the elements beneficial to strength (Mo, Sn) were not uniformly distributed, and the influence on graphite size and pearlite interlammer spacing was not obvious, resulted in poor mechanical properties.